A 5-year Study of Systemic Reactions Using both Shared and Patient-Specific Vaccines. Issue 2 (September 2013) - Melamed, Julian; Mehra, Ami; Ahuja-Malik, Angela
The safety of shared specific vaccines (SSVs) has been questioned by some experts. The purpose of this study was to evaluate the safety of SSVs. Details of systemic allergic reactions after subcutaneous immunotherapy injections were captured on a standardized form from July 2005 to July 2010. Patient records were evaluated for factors that might be associated with increased rate of systemic reactions and, in addition, were examined for any errors. Systemic reaction rates (SRRs) using a combination of shared and patient-specific vaccines (PSVs) were similar to previously reported studies (0.23 reactions per 100 shots). There were no systemic reactions resulting from errors where the incorrect shared allergen was administered, but we did note one reaction after an erroneously administered PSV. There were two dosage errors associated with both shared and patient-specific immunotherapy. Most reactions were mild to moderate (World Allergy Organization grade, 1 or 2). Severe reactions with 911 activations were noted in six patients. Thirty percent of reactions occurred out of the office and the average time to reaction was 48 minutes. Epinephrine was administered in only 60% of patients. Epicutaneous reactivity to mites, cats, dogs, and pollen but not mold occurred significantly more in reactors. Differences in SRRs were encountered between satellite offices. Using a combination of SSV and PSV, SRRs were similar to previously reported studies; moreover, no systemic reactions occurred where a SSV was erroneously administered. SRR surveillance is a useful safety tool.